2020
DOI: 10.33225/pec/20.78.48
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between School Culture Sub-Categories and Expected Results of Learning Process

Abstract: The aim of the research was to find out what factors of school culture affect the expected results of teaching and learning processes in basic schools. The research evaluated current and desired school culture in selected basic schools to identify culture gaps. Research using School Culture Inventory explored relations among selected sub-categories, namely between the sub-categories focused on shared objectives, trust in school leadership, and on managerial approach and the important sub-categories focused on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
2
8
0
2
Order By: Relevance
“…In the study by Clark (2019), it was found that there was a strong relationship between school culture and its outcomes, revealing that schools having positive cultures have positive outcomes among their students and staff than those that do not. Eger and Prasilova (2020) examined what factors of school culture affect the expected results of teaching and learning processes and discovered that the leadership and management's role was one of the most crucial factors for shaping the school culture. Duan et al (2018) put forth that schools with stronger cultures have satisfied teachers, along with higher school effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Clark (2019), it was found that there was a strong relationship between school culture and its outcomes, revealing that schools having positive cultures have positive outcomes among their students and staff than those that do not. Eger and Prasilova (2020) examined what factors of school culture affect the expected results of teaching and learning processes and discovered that the leadership and management's role was one of the most crucial factors for shaping the school culture. Duan et al (2018) put forth that schools with stronger cultures have satisfied teachers, along with higher school effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important that school leaders use effective management strategies which will direct the staff to work towards common goals and encourage coordination among all members of the school. In order to improve school culture, it is essential for school leaders to pay attention to the communication within the school which impacts the teaching and learning processes of the school (Eger & Prasilova, 2020). Accordingly, the voice of the teachers needs to be heard when making pedagogical and educational decisions (Vieira & Brabosa, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Given the context of the Czech Republic, it does not address the dimension of multicultural orientation. The study focuses on the dimensions of school culture within Czech schools and follows a pilot study by Eger and Prášilová (2020). The theoretical construct of this research was prepared on the basis of a literature review (among others, Bush, 2003;Everard, Morris and Wilson, 2004;Fidler, 2002;Gruenert, 2000;Maslowski, 2006;Peterson and Deal, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Naproti tomu kulturu nelze jednoduše vnímat, jedinec se postupně stává její součástí, kultura ale významně ovlivňuje to, jak se ve škole věci dělají, což opět souvisí i s tématem naší studie. Nic-méně, předchozí studie (Eger & Prášilová, 2020) ukázala, že studenti po souvislé praxi umí s využitím vhodného nástroje (Maslowski, 2006) posoudit kulturu školy, kde praxi vykonávali. Samozřejmě s omezením, že se jednalo o měsíční pobyt ve škole na straně jedné, ale s výhodou, že byli přímo aktivními aktéry života v té dané škole.…”
Section: Adaptace V Organizačním Prostředíunclassified